FADS1 genotype is distinguished by human subcutaneous adipose tissue fatty acids, but not inflammatory gene expression - Klingel, Shannon L; Valsesia, Armand; Astrup, Arne; Kunesova, Marie; Saris, Wim H M; Langin, Dominique; Viguerie, Nathalie; Mutch, David M (International journal of obesity, 2019)
BACKGROUND: Single nucleotide polymorphisms (SNPs) in FADS1/FADS2 genes are associated with changes in serum and tissue polyunsaturated fatty acid (PUFA) content. PUFA regulate inflammatory signaling pathways in adipose tissue; however, the effect of SNPs in FADS1/FADS2 on adipose tissue inflammation is equivocal. The present study examined if SNPs in FADS1/FADS2 modify human subcutaneous adipose tissue (SAT) fatty acid profiles and the expression of genes associated with inflammation/immune function, lipid metabolism, and cellular differentiation. METHODS: SAT fatty acids and the expression of 117 genes were measured in 174 men and women from the DiOGenes Study using gas chromatography and qRT-PCR, respectively. Associations between fatty acids, gene expression, and SNPs in FADS1/FADS2 were investigated by linear regression and multivariate analysis. RESULTS: Four SNPs (rs174537, rs174546, rs174556, rs174601) in FADS1/FADS2 were significantly associated with SAT fatty acids. All SNPs were in high linkage disequilibrium with the commonly reported rs174537 SNP in FADS1. Minor allele carriers for rs174537 (GT+TT) had reduced 20:4n-6 (p = 1.74E-5), lower delta-5 desaturase enzyme activity (p = 2.09E-9), and lower FADS1 gene expression (p = 0.03) compared to major GG carriers. Multivariate analysis revealed that 20:4n-6 and 20:3n-6 explained ~19% of the variance between rs174537 genotypes, while gene expression explained <7%. Receiver operating characteristic (ROC) curves indicated that rs174537 genotype can be distinguished with SAT fatty acids (AUC = 0.842), but not gene expression (AUC = 0.627). No differences in SAT inflammatory gene expression were observed between rs174537 genotypes. SAT 20:3n-6 levels were positively correlated with the expression of several inflammatory genes, and inversely correlated with FADS1 expression. CONCLUSION: This study showed that FADS1 genotype is distinguished by SAT fatty acid profiles, but not inflammatory gene expression.
Keywords: buněčná diferenciace; mastné kyseliny; mužské pohlaví; multigenová rodina; Male; Cell Differentiation; imunitní systém; Female; Humans; Inflammation; metabolismus lipidů; zánět; Genotype; Gene Expression; Lipid Metabolism; lidé; Polymorphism, Single Nucleotide; Immune System; Middle Aged; ženské pohlaví; lidé středního věku; jednonukleotidový polymorfismus; desaturasy mastných kyselin; lineární modely; exprese genu; Fatty Acids; obezita; Obesity; Multigene Family; Subcutaneous Fat; genotyp; podkožní tuk; Fatty Acid Desaturases; Multivariate Analysis; dospělí; Adult; multivariační analýza; Linear Models